Single-cell transcriptomics unravels the early immune landscape of renal allograft rejection and nominates Ccl3-Ccr5 as a therapeutic target - Wei, Fanchao; Wang, Zhaoxiang; Qi, Ruochen; Zhang, Jingliang; Han, Shichao; Shi, Changhong; Lu, Tong; Zhao, Zhite; Li, Zhengxuan; Li, Lang; Qin, Weijun; Ma, Shuaijun; et al. (Frontiers in Immunology, 2025)
BackgroundAcute rejection is a significant cause of impaired graft survival in the early post-transplantation period, and the early-stage immune cell dynamics with local intercellular communication during this process require further elucidation.MethodsWe performed single-cell RNA sequencing (scRNA-seq) on CD45+ immune cells isolated from rat renal allografts during the early phase of acute rejection (days 0, 1, 3, and 7). Using unsupervised clustering, functional enrichment analysis, cellular trajectory inference, and intercellular communication network mapping, we delineated the immune cell dynamics and local communication networks at single-cell resolution. Our findings were subsequently validated through multiplex immunofluorescence and therapeutic intervention experiments.ResultsMacrophages constituted the dominant immune population during acute rejection. Sub-clustering analysis revealed a rapid expansion of the Isg15+Mac subset by post-transplant day 1, which persisted at elevated levels thereafter. Functional enrichment and trajectory inference demonstrated the pro-inflammatory properties of Isg15+Mac, implicating this subset in acute rejection. Cell-cell communication analysis identified Ccl3-Ccr5 ligand-receptor interactions between Isg15+Mac and T cells. Multiplex immunofluorescence confirmed abundance of Isg15+Mac within the allografts. Moreover, the acute rejection after kidney transplantation was alleviated by the FDA-approved Ccr5 blocker Maraviroc.ConclusionsOur study establishes an in-depth, early-stage immune landscape of renal transplantation, revealed that the Isg15+Mac subset activates T cells via the Ccl3–Ccr5 axis and thereby serves as a critical driver of acute rejection. And indicating that Maraviroc may potentially be a therapeutic candidate for transplant rejection.